2006
DOI: 10.4049/jimmunol.176.2.1053
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Cleavage of Antigenic Peptides Either by the Immunoproteasome or by the Standard Proteasome Results in Differential Antigen Presentation

Abstract: The immunoproteasome (IP) is usually viewed as favoring the production of antigenic peptides presented by MHC class I molecules, mainly because of its higher cleavage activity after hydrophobic residues, referred to as the chymotrypsin-like activity. However, some peptides have been found to be better produced by the standard proteasome. The mechanism of this differential processing has not been described. By studying the processing of three tumor antigenic peptides of clinical interest, we demonstrate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
131
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 52 publications
8
131
0
1
Order By: Relevance
“…Our results strongly suggest that the influenza matrix M1 58-66 epitope is destroyed by b5 and can be rescued by a b5 inhibitor and, thus, LMP7 induction protects the CTL epitope from destruction by b5. In line with our results are the data from Chapiro et al (43), which demonstrated that the MAGE-C2 336-344 peptide is produced by the immunoproteasome, but not by the constitutive proteasome, because the latter destroys the Ag by making an internal cleavage occurring after an acidic residue.…”
Section: Discussionsupporting
confidence: 82%
“…Our results strongly suggest that the influenza matrix M1 58-66 epitope is destroyed by b5 and can be rescued by a b5 inhibitor and, thus, LMP7 induction protects the CTL epitope from destruction by b5. In line with our results are the data from Chapiro et al (43), which demonstrated that the MAGE-C2 336-344 peptide is produced by the immunoproteasome, but not by the constitutive proteasome, because the latter destroys the Ag by making an internal cleavage occurring after an acidic residue.…”
Section: Discussionsupporting
confidence: 82%
“…We conclude that the crosspresentation of the gp100 peptide is mostly independent of the proteasome. It has been described previously that these two epitopes are cleaved in vitro by purified immunoproteasome [42,43]. It is also known that both immature and mature DC contain immunoproteasomes.…”
mentioning
confidence: 94%
“…Further dilutions were performed in PBS. The MelanA/MART-1 short (EAAGIGILTV) or long (KGHGHSYTTAEEAAGIGILTVILGVL) peptides [43] and the gp100 short (IMDQVPFSV) or long (AHSSSAF-TIMDQVPFSVSVSQLR) peptides [60] were used. An additional synthesis of the long MelanA peptide includes an N-terminal biotin.…”
mentioning
confidence: 99%
“…34 Second, IFN-g gave a marginal effect on E6 mRNA expression, but its favorable effect on increased cell surface expression of HLA class I molecules was evident in most cell lines tested, which is critical for efficient recognition by CD8 1 T cells. Nevertheless, it is likely that IFN-g treatment facilitated either active destruction of the E6 49-57 epitope or failure in epitope generation by immunoproteasome, 42 which is induced by IFN-g as observed in IFN-gtreated SiHa/E6-E7 cells. It remains to be determined in the future whether IFN-g secreted from tumor-reactive CTLs might unexpectedly allow tumor cells to escape by further reducing the amount of epitopes possessing kinetics similar to E6 [49][50][51][52][53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%